Uncovering the Minor Contribution of Land‐Cover Change in Upland Forests to the Net Carbon Footprint of a Boreal Hydroelectric Reservoir. Issue 4 (1st July 2015) - Dessureault, Pierre‐Luc; Boucher, Jean‐François; Tremblay, Pascal; Bouchard, Sylvie; Villeneuve, Claude
Abstract : Hydropower in boreal conditions is generally considered the energy source emitting the least greenhouse gas per kilowatt‐hour during its life cycle. The purpose of this study was to assess the relative contribution of the land‐use change on the modification of the carbon sinks and sources following the flooding of upland forested territories to create the Eastmain‐1 hydroelectric reservoir in Quebec's boreal forest using Carbon Budget Model of the Canadian Forest Sector. Results suggest a carbon sink loss after 100 yr of 300, 000 ± 100, 000 Mg CO2 equivalents (CO2 e). A wildfire sensitivity analysis revealed that the ecosystem would have acted as a carbon sink as long as <75% of the territory had burned over the 100‐yr‐long period. Our long‐term net carbon flux estimate resulted in emissions of 4 ± 2 g CO2 e kWh −1 as a contribution to the carbon footprint calculation, one‐eighth what was obtained in a recent study that used less precise and less sensitive estimates. Consequently, this study significantly reduces the reported net carbon footprint of this reservoir and reveals how negligible the relative contribution of the land‐use change in upland forests to the total net carbon footprint of a hydroelectric reservoir in the boreal zone can be.